Efektivitas program pengembangan kepribadian melalui pembelajaran eksperiensial dalam peningkatan keunggulan sumber daya praja IPDN - Dewi, Mutiar Fitri; Wangsih, Wangsih (Jurnal Pendidikan Karakter, 2022)
This study aims to obtain a realistic description of the effectiveness of personality development programs through experiential learning in increasing the superiority of student resources in the environment of Institute of Domestic Administration (IPDN) Jatinangor Campus, Sumedang. This study focuses on personality development (self-development program) and experiential learning. This research is field research with a qualitative descriptive method, which only describes what it is about the effectiveness of the experiential method in personality development programs to increase the superiority of student resources. The subjects of the study were students, namely young students, a total of 20 people representing various study programs and two observers. The object of the research is experiential learning with 5 (five) aspects of personality development: self-confidence, communication, interpersonal relations, leadership, and managing stress. Data is collected through the provision of training or learning, observation, questionnaires, and interviews. After being analyzed, the results show that experiential learning is very effective in personality development programs for increasing the excellence of student resources at IPDN Jatinangor Sumedang. From the data analysis it can be concluded that the effectiveness of experiential learning is in the high category.